Kemampuan Guru Menerapkan Penguatan Pendidikan Karakter (PPK) Berbasis Kelas di UPT SPF SDN Melayu Muhammadiyah Kota Makassar - Salvia Salmawati; Hasibuddin, Hasibuddin; Pilo, Nashiruddin (Journal of Gurutta Education, 2023)
The purpose of this study was to determine the form of strengthening character education in learning at UPT SPF SDN Melayu Muhammadiyah, Wajo District, Makassar City. This research uses a descriptive qualitative research type. The research subjects were school principals, teachers, and UPT SPF students at SDN Melayu Muhammadiyah, Wajo District, Makassar City. Research instruments using interviews, observation, and documentation. Data analysis techniques use qualitative data analysis techniques which consist of data collection, data condensation, data display, and data verification. The results of the study show that, (1) religious values are reflected in congregational prayer activities which are carried out every day before going home from school; (2) the nationalist values shown by students are reflected when carrying out ceremonies in earnest, as well as getting used to singing one of the national obligatory songs before starting learning; (3) the value of independence shown by students is reflected in the activities of doing assignments given by the teacher carried out independently, and avoiding cheating activities; (4) the value of gotong royong is reflected when students work together to clean the classroom and school grounds